Self-regulation of learning and its interface for the development of students of the pedagogy course in distance education of UNINASSAU - Gomes , Charles Everton Oliveira; Martins , Charles Gomes; Simões, José Luís (Seven Editora, 2023)
The research carried out aimed to analyze the self-regulation of learning and its interface for the development of Pedagogy students in distance education of the Ser Educacional Group. After analyzing the data, we can conclude that there was an interface of the principles adopted by the institution that contributed to the development of students. We interviewed 322 students and we highlight that the majority of students are female. This may be a striking feature of Pedagogy courses in Brazil. The 8th period students showed evidence that they mostly adopted learning strategies in their study routine. We also saw that the VLE (Virtual Learning Environment) enhances the development of strategies and can foster new habits and biopsychosocial development in students. DOI:https://doi.org/10.56238/ptoketheeducati-073